Combination of bio-organo-mineral fertilizers on optimizing the growth and production of tomatoes (Solanum lycopersicum L.) in dryland environment - Alfassabiq Khairi; Jayaputra; Padusung; Sri Tejowulan; Nurrachman (Universitas Lancang Kuning, 2023)
Mineral or inorganic fertilizers are increasingly being used to increase tomato productivity. However, excessive use of inorganic fertilizers may negatively impact soil fertility and microbial activity. To maintain food safety and agricultural sustainability, the use of inorganic fertilizers must be balanced with organic fertilizers. Additionally, sub-optimal land, such as dryland, can be used to optimize tomato productivity, particularly in the North Lombok Regency, Indonesia. This study aimed to investigate the effect and interaction of a combination of liquid organic fertilizer (LOF), plant growth regulator (PGR), and NPK fertilizers as inorganic fertilizers on the growth and yield of tomatoes in dryland. The experimental design was a completely randomized block design, with two factors: the concentrations of commercial inorganic fertilizer (0, 1,300, and 2,600 ppm) and the type of commercial LOF (Bio-Extrim and Organox) + commercial PGR (Hormax). The results showed that the interaction was not significantly different between inorganic fertilizer and LOF + PGR, except for mean fruit weight in the first week of harvest. However, there were differences in responses at the level of each factor. The application of inorganic fertilizer at 2,600 ppm increased tomato productivity by 13.81%. LOF was only significantly different in fruit weight/plant in the first week of harvest and was not significant after that.